(untitled) (Comparative & International Education Series, 2022)
Research in Canada has focused on international students’ experiences of employment following graduation from an academic program. This chapter, however, examines the experiences of a multilingual international student from Brazil prior to the beginning of her academic studies at a Canadian university. Based on a narrative inquiry approach, this chapter brings to light the challenges the student encountered in the following domains: inferiorisation on the basis of language proficiency; lack of Canadian-based work experience and of a professional network; and lastly, marginalisation based on her foreignised status, which led to feelings of exploitation and voicelessness. By discussing the student’s experiences, this chapter foregrounds the potential needs of multilingual international students from the global south with respect to employment-related experiences specifically before commencing their studies in Canada and in similar contexts.